CHALLENGES FACING YEMEN REFUGEE WOMEN IN ADDIS ABABA, ETHIOPIA - ADAMEK, Margaret; AMARE, Samuel; MINAYE, Abebaw (Journal of Social Sciences, 2023)
Forced migration is associated with several challenges. The challenges that refugee women faced in their host countries were numerous. There has been a gender bias in Ethiopian literature on refugees. Refugees are homogenized in the existing studies. The gender differences among refugees have an impact on the challenges of forced migration that they encounter and how they handle them. Moreover, no study has been done on the adaptation challenges faced by Yemeni refugee women in Addis Ababa. This study's main objective was to examine the challenges that Yemeni refugee women faced in Addis Ababa. An interpretative phenomenological analysis was employed to achieve that objective. Thirteen Yemeni refugee women were interviewed using a semi-structured interview guide to understand their experiences. Purposive sampling was used to choose study participants. The data was analyzed using interpretive phenomenological analysis procedures. The study's findings revealed that refugee women encountered several challenges that were detrimental to their well-being, including language difficulties, limited income and job opportunities, unrecognized identity papers and price increases, and housing problems. Furthermore, refugee women faced social isolation and sexual harassment. The study concluded that the challenges that Yemeni refugee women faced in Addis Ababa had an enormous impact on their well-being, which demands immediate intervention.